Why startups fail in emerging entrepreneurial ecosystems? - D'Andrea, Fernando Antonio Monteiro Christoph; Santos, Diego Alex Gazaro dos; Costa, César Vinícius Pereira; Zen, Aurora Carneiro (REGEPE Entrepreneurship and Small Business Journal, 2023)
Objective: Entrepreneurs are responsible for innovation, but they do not act in the vacuum, the greater the support for their action, the improve the chances of success. Startups - technology-based companies with high potential for growth and impact - are associated with the existence of entrepreneurial ecosystems that facilitate entrepreneurial action. This paper goal is to provide evidence that help to explain why startups fail in an emerging entrepreneurial ecosystem. Method: We perform exploratory research in which entrepreneurs whose startups failed in the emerging entrepreneurial ecosystem of Porto Alegre, Brazil, were interviewed. We complement the analysis with the collection of secondary data. Results: Building on Isenberg’s (2011) six domains, we generate ideas on how each of them in emergent entrepreneurial ecosystem may influence startup mortality. Our results indicate that emerging entrepreneurial ecosystem could be much better in avoiding the premature failure of startups. Policy and Finance are the most problematic domains, while culture, support, and markets are the three middle-ground dimensions. These last three need improvement, but they are not as critical as the first two. Contributions: This paper contributes to the entrepreneurial ecosystems literature by exploring how emergent ecosystems contribute for discontinuity of promising startups. Originality: Besides entrepreneurial mistakes, problems that are out of the entrepreneur control can also cause a venture's death (Cardon et al., 2011). Building on this, we use Isenberg's (2010; 2011) model for understanding the influence of the entrepreneurial ecosystem on the circumstances that entrepreneurs faced that determined their startup failure (Jenkins & McKelvie, 2016). Social Contributions: by better understanding why startups fail in emerging entrepreneurial ecosystems, we support policymakers in their focus on possible improvements of the features that seem most relevant to entrepreneurs. The public agents can then work to provide a better environment for future entrepreneurial endeavors.